Who Benefits Most From Head Start? Using Latent Class Moderation to Examine Differential Treatment Effects. Issue 6 (11th August 2014) - Cooper, Brittany Rhoades; Lanza, Stephanie T.
<x xml:space="preserve">Abstract</x> Head Start (HS) is the largest federally funded preschool program for disadvantaged children. Research has shown relatively small impacts on cognitive and social skills; therefore, some have questioned its effectiveness. Using data from the Head Start Impact Study (3‐year‐old cohort; N = 2, 449), latent class analysis was used to (a) identify subgroups of children defined by baseline characteristics of their home environment and caregiver and (b) test whether the effects of HS on cognitive, and behavioral and relationship skills over 2 years differed across subgroups. The results suggest that the effectiveness of HS varies quite substantially. For some children there appears to be a significant, and in some cases, long‐term, positive impact. For others there is little to no effect.